PENGEMBANGAN MEDIA PERMAINAN SPIN (RODA PUTAR) PADA MATERI BANGUN DATAR SISWA KELAS IV SEKOLAH DASAR NEGERI 6 RAMBANG - Yolanda Tri Septiani; Destiniar; Putri Dewi Nurhasana (STKIP Subang, 2023)
This study aims to produce a learning product in the form of a spin game media (swivel wheel) on flat shape material forgrade IV elementary school students that is valid, practical, andeffective. The type of research conducted is Research & Development (R&D) with the development model used, namely the ADDIE model. The results showed that: 1) The quality of the swivel wheel media seen from the aspect of validity was included in the